The atlas of endangered places - Pollock, Steve (Stephen Thomas) (New York : Facts on File, 1993)
Text, photographs, and maps focus on areas of the world in which human activity is destroying the natural balance.
South America -- Tropical forest destruction -- The Mediterranean -- East Europe -- Freshwater pollution -- Northern Africa -- Desertification -- War in the Gulf -- Deforestation and soil erosion -- Southeast Asia -- Global warming.
Includes indexes and glossary.
"First published in the UK in 1993 by Belitha Press Limited"--T.p. verso.
Bibliography p: 60.
Booklist.
Library Talk.
School Library Journal.
Keywords: Children's atlases; Man -- Influence on nature -- Juvenile literature; Man -- Influence on nature -- Maps -- Juvenile literature; Pollution -- Juvenile literature; Pollution -- Maps -- Juvenile literature; Man -- Influence on nature; Man -- Influence on nature -- Maps; Pollution; Pollution -- Maps; Human influence on nature; Human influence on nature -- Maps; Pollution; Pollution -- Maps